2004
DOI: 10.1111/j.1440-1746.2004.03251.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost of outpatient care in patients with inflammatory bowel disease in a German University Hospital

Abstract: This is the first time that the structure and range of outpatient treatment costs for IBD have been demonstrated for a German hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 20 publications
0
30
0
4
Order By: Relevance
“…Crohn's disease is also very important for both the people suffering from the severe chronical illness with all its painful and difficult attributes and for the huge expenditure for treatment and additional costs (Juan et al, 2003;Bassi et al, 2004;Ebinger et al, 2004). Information already available is sufficient to accept the possibility of a risk for consumers resulting not only from the viable MAP, but also from inactive or dead cells and even from their structural components.…”
Section: Discussionmentioning
confidence: 99%
“…Crohn's disease is also very important for both the people suffering from the severe chronical illness with all its painful and difficult attributes and for the huge expenditure for treatment and additional costs (Juan et al, 2003;Bassi et al, 2004;Ebinger et al, 2004). Information already available is sufficient to accept the possibility of a risk for consumers resulting not only from the viable MAP, but also from inactive or dead cells and even from their structural components.…”
Section: Discussionmentioning
confidence: 99%
“…This may partially explain the trend we observed in the prevalence of irondeficiency anemia and the higher prevalence of anemia in our study than in others. [28][29][30] In the present study anemia was related to disease activity in both Crohn's disease and ulcerative colitis (Figure 2). Greater disease activity in anemic patients with Crohn's disease has been previously reported.…”
Section: Crohn's Disease Ulcerative Colitis Type Of Anemia Diagnosis mentioning
confidence: 99%
“…Some studies have reported increased effectiveness in treating ulcerative proctitis and proctosigmoiditis by combining oral 5-ASA compounds with Rowasa enemas. Oral 5-ASA compounds are also used to maintain remission in ulcerative proctitis and proctosigmoiditis [30] . Another alternative for patients who fail to respond to Rowasa or who cannot use Rowasa is cortisone enemas (Cortenema).…”
Section: Rowasa Enemamentioning
confidence: 99%
“…Rowasa is 5-ASA compound mesalamine in enema form and is effective in the treatment of ulcerative proctitis and ulcerative proctosigmoiditis (two conditions where active 5-ASA drugs taken as enemas can easily reach the inflamed tissues directly) [29,30] . Each Rowasa enema contains 4 g of mesalamine in 60 mL of fluid.…”
Section: Rowasa Enemamentioning
confidence: 99%